Vortex matter freezing in Bi2Sr2CaCu28 samples with a very dense distribution of columnar defects - Cejas Bolecek, N.R.; Kolton, A.B.; Konczykowski, M.; Pastoriza, H.; Dominguez, D.; Fasano, Y.; Fasano, Yanina (American Physical Society, 2016)
Fil: Cejas Bolecek, N.R. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina